Please Accept My Sincerest Apologies: Examining Follower Reactions to Leader Apology - Basford, Tessa E.; Offermann, Lynn R.; Behrend, Tara S. (2014)
Recognizing gaps in our present understanding of leader apologies, this investigation examines how followers appraise leader apologies and how these perceptions impact work-related outcomes. Results indicate that followers who viewed their leader as trustworthy or caring before a leader wrongdoing were more likely to perceive their leader’s apology to be sincere, as compared to followers who previously doubted their leader’s trustworthiness and caring. Attributions of apology sincerity affected follower reactions, with followers perceiving sincere apologies reporting greater trust in leadership, satisfaction with supervision, leader–member exchange quality, affective organizational commitment, and forgiveness than those reporting insincere or no apologies. A mediation model was supported, showing that attributions of apology sincerity fostered perceptions of humility, which enhanced perceptions of transformational leadership, and consequently garnered more positive follower reactions.
Keywords: Followership; Leadership; Apology